INFLUENCE OF SUPPLIER QUALITY COMMITMENT ON THE PERFORMANCE OF STATE CORPORATIONS IN KENYA - Wachiuri, Elizabeth Wangu; Waiganjo, Dr. Esther; Ismail, Dr. Noor; Odhiambo, Prof. Romanus (International Journal of Supply Chain Management, 2017)
Purpose: The purpose of this study was to establish the influence of supplier quality commitment on the performance of state corporations in Kenya. Methodology: The study adopted cross-sectional survey design using both quantitative and qualitative approaches. The target population was all the 187 state corporations in Kenya. The study employed a census approach. Primary data was collected using questionnaires. A pilot study was conducted to measure the research instruments reliability and validity. Descriptive statistics were used aided by Statistical Packages for Social Sciences version 24 to compute percentages of respondents' answers. Inferential statistics using linear regression and correlation analysis were applied to assist examining relationship between the research variables. The results were presented using tables and graphs. Results: The study findings revealed that supplier quality commitment explained 34.6% of the total variations in performance of state corporations in Kenya. Further, results indicate that the overall model was statistically significant as supported by a p value of 0.000. This was supported by an F statistic of 74.994 and the reported p value (0.000) which was less than the conventional probability of 0.05 significance level. In addition, the study findings show that there is a positive and significant relationship between supplier quality commitment and performance of state corporations in Kenya as supported by a p value of 0.000 and a beta coefficient of (0.793). This implies that an increase in supplier quality commitment by 1 unit would increase the performance of state corporations by 0.793 units. Unique contribution to theory, practice and policy: Based on the findings, the study recommended that organizations should consider the following quality dimensions; management commitment, product development, process improvement, quality planning and quality assurance in supply chain, quality assessment in production, inspection and experimentation and quality staff of supplier. The improvement of the mentioned quality aspects will lead to improved service provision by suppliers, which will translate into increased performance of state corporations. Also it's important to check the supplier's reliability in terms of timeliness and also check if suppliers are in conformance with ISO standards.